PENGARUH CSR BERDASAR ISO 26000 TERHADAP NILAI PERUSAHAAN DENGAN KARAKTERSITIK PERUSAHAAN SEBAGAI VARIABEL MODERATING - Latifah, Sri Wahjuni (Journal of Innovation in Business and Economics, 2015)
Research of the influence of ISO 26000 CSR toward the company's value as a moderating variable which is done on companies listed in Indonesia Stock Exchange. The Company’s characteristics are measured by firm age, size, leverage and profitability. The data analysis was done by using double linear regression models, the first is to see the effect based on the ISO 26000 CSR and firm characteristics on value, and the second is to see the effect of interaction with the ISO 26000 corporate characteristics. The results of the study showed that there was no influence of ISO 26000, the characteristics of the company toward the value of the company. However, moderated ISO 26000 by firm characteristics affect the value of the company.